Method Development And Validation For Estimation Of Commercially Produced Sex Pheromones In Lure (Journal of the Bangladesh Chemical Society, 2013)
A method was developed and validated for quantitation of methyl eugenol and cuelure, the active ingredients of two formulated sex pheromones (bio-pesticides) Mukti and Jhilik by gas chromatography. Technical grade methyl eugenol and cuelure (purity 95- 96%) were used as standards. Calibration curves of methyl eugenol and cuelure were linear with correlation coefficient (r2) 0.9966 & 0.9988, respectively. Ten replicate analyses were done for both methyl eugenol & cuelure and quantity of the pheromones in the two formulated products were found to be 0.55 ± 0.11 and 0.56 ± 0.09 g/lure (Mean ± SD), respectively. The stability of both pheromones in solution and their diffusion from lures under UV-Vis light was determined for a period of 21 days. The results showed that diffusion of the both pheromones from lure were very fast and about two-third diffused within 10 days after exposure. Methyl eugenol was quite stable in solution, whereas cuelure was found to degrade slowly, and about 15 % cuelure degraded within 21 days. The recovery of methyl eugenol and cuelure from matrix were found to be 80.69 ± 3.14 and 78.48 ± 4.32 % (mean ± SD), respectively, where limit of detection (LOD) & limit of quantification (LOQ) were found to be 97 & 80 ppm, and 290 & 240 ppm, respectively. The developed method is very simple and can be used for estimation of the two sex pheromones. Journal of Bangladesh Chemical Society, Vol. 25(2), 180-185, 2012 DOI: http://dx.doi.org/10.3329/jbcs.v25i2.15084